Watching water birds - Arnosky, Jim (National Geographic Society ; Distributed by Publishers Group West, 1997)
Provides a personal look at various species of fresh- and saltwater birds, including loons and grebes, mergansers, mallards, wood ducks, Canada geese, gulls, and herons.